Controllable size and crystallinity of Ru nanoparticles on a carbon support synthesized by fluidized bed reactor-atomic layer deposition for enhanced hydrogen oxidation activity - Lee, Woo Jae; Bera, Susanta; Woo, Hyun Jae; An, Jung Won; Bae, Jong Seong; Oh, Il Kwon; Kwon, Se Hun (Journal of Materials Chemistry A, 2021)
Low-temperature fuel cells have attracted significant attention owing to their low cost and high performance. Herein, uniform Ru nanoparticles (NPs) with various size distributions were synthesized as a non-Pt catalyst on a carbon support by fluidized bed reactor-atomic layer deposition (FBR-ALD) as a function of ALD cycles for the hydrogen oxidation reaction (HOR) in alkaline medium. With an increase in the number of ALD cycles from 5 to 30 cycles, the wt% of the Ru NPs increased from ∼5 to ∼32 wt%. In addition, the structural characterization of the Ru NPs revealed the formation of Ru NPs with a uniform, dense, and controllable size (∼2-4 nm) and crystallinity depending on the growth cycle of ALD. However, the 10 cycled Ru catalyst with a NP size of ∼2 nm possessed a highly electrochemically active roughened surface (amorphous moiety covered the crystallite), which enhanced its HOR and mass activity. Remarkably, the ALD-synthesized Ru catalyst outperformed a commercial Ru/C catalyst with a similar wt%. Hydrogen binding energy (HBE) calculations revealed that the specific activity of the catalyst increased with decreasing HBE. The mechanistic pathway for the HOR indeed illustrates that enhanced activity under alkaline conditions was found owing to the weakening of the metal-H interaction influenced by the Ru NP crystallinity and size. The findings of this study indicate that the FBR-ALD technique is an effective, scalable approach for the synthesis of active non-Pt metal catalysts.
Keywords: Alkaline conditions; Fluidized bed reactors; Hydrogen oxidation; Hydrogen oxidation reaction; Low temperature fuel cells; Mechanistic pathways; Roughened surfaces; Structural characterization